The Phantom Regiment; or, Stories of "Ours" - Grant, James, 1822-1887 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Phantom Regiment; or, Stories of 'Ours'" by James Grant is a fictional novel written in the late 19th century. This work explores themes of romance, military life, and adventure, centering around the character Ricardo Ramble, a British officer stationed in Gibraltar. The story unfolds as Ramble reminisces about a brief romantic encounter with a beautiful Spanish woman named Paulina, leading to a mix of personal drama and the broader backdrop of military tensions. The opening of the novel introduces readers to the protagonist, Lieutenant Richard Ramble, reflecting on a bittersweet farewell to Donna Paulina and her mother, who are departing for Spain. As he navigates his feelings of loss, Ramble is encouraged by his friend, Jack Slingsby, to move on with life at the garrison. Their camaraderie is evident amidst the garrison's gossipy atmosphere, and hints at Ramble's desire for adventure emerge as the narrative shifts toward his aspirations and the anticipated deployment to the war in the Crimea. The tone blends romance with military banter, setting the stage for a tale rich in character interactions and explorations of love and duty. (This is an automatically generated summary.)
Release date is 2021-05-20
Al Haines
Keywords: Soldiers -- Fiction; Adventure stories; British -- Foreign countries -- Fiction